Pengaruh Lingkungan Kerja terhadap Kepuasan Kerja Pada PT. Dhamar Tunggul Wulung Kota Kediri - Bagus Helmi Dharmawan; Rusdi Hidayat Nugroho (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to examine the effect of the physical work environment and non-physical work environment on job satisfaction either simultaneously or partially. The approach used in this study is quantitative with a saturated sampling technique of about 30 respondents from office employees at PT. Dhamar Tunggul Wulung Kediri City, and data collection using questionnaires with Likert scale measurements. Multiple regression analysis using SPSS software version 25 for windows was used to test the hypothesis of the study. The results of this study indicate that the physical work environment and non-physical work environment simultaneously or jointly have a significant effect on employee job satisfaction, the physical work environment has a positive and significant effect on employee job satisfaction, while the non-physical work environment has no significant effect on employee job satisfaction. . The value of the coefficient of determination in this study is 72.7%, this means that this research model can explain 72.7% of employee job satisfaction, while the remaining 27.3% is explained by other variables not explained in this study. Keywords: Physical Working Environment, Non-Pyhsical Working Environment, and Employee Satisfaction